2010
DOI: 10.3109/02699052.2010.494592
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based statistical analysis of thalamic glucose metabolism in traumatic brain injury: Relationship with consciousness and cognition

Abstract: Lull Noguera, N.; Noé, E.; Lull Noguera, JJ.; Garcia Panach, J.; Chirivella, J.; Ferri, J.; López-Aznar, D.... (2010). Voxel-based statistical analysis of thalamic glucose metabolism in traumatic brain injury: relationship with consciousness and cognition. Brain Injury. 24(9): 1098-1107. doi:10.3109/02699052.2010.494592. XML Template (2010) [4.6.2010 [ AbstractObjective: To study the relationship between thalamic glucose metabolism and neurological outcome after severe traumatic brain injury (TBI). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 48 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…29 Two SPECT and 4 PET studies evaluated patients with TBI separately (table e-2). 32,36,41,43,47,48 In one study of comatose patients with TBI, a global reduction in activity was noted with minimal variation across ROIs compared with HCs. 47 This reduction was noted to be highly significant in the brainstem, striatum, and thalamus in another coma TBI study.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Two SPECT and 4 PET studies evaluated patients with TBI separately (table e-2). 32,36,41,43,47,48 In one study of comatose patients with TBI, a global reduction in activity was noted with minimal variation across ROIs compared with HCs. 47 This reduction was noted to be highly significant in the brainstem, striatum, and thalamus in another coma TBI study.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…These studies showed widespread reductions in activity in parietal, occipital, frontal, insular and cingulate cortices, and in the thalamus (findings of each study are listed in detail in table e-3). 26,29,31,32,35,36,38,41,42 In several studies, when compared with subjects in the MCS, patients in VS had proportionally greater reductions in activity in the precuneus and in the posterior cingulate cortex (PCC). 26,35,39 This reduction in activity in the precuneus was coupled with increased activity in brainstem arousal centers in one study.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the thalamus in DOC has also been explored. Thalamic metabolism has been shown to be depressed in a way correlating with the level of consciousness, as detected with behavioural examinations [3,15,16]. Interestingly, restoration of thalamocortical connectivity has been associated with recovery of a patient in chronic VS/UWS [17].…”
Section: Introductionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose-positron emission tomography (FDG-PET) i maging studies have shown that the recovery of global m etabolic activity might not be required for regaining consciousness in DOCs patients. These studies have identified a fronto-parietal network encompassing midline (i.e., anterior cingulate/mesiofrontal and posterior cingulate/precuneus) and lateral (i.e., prefrontal and posterior parietal) associative cortices that is consistently hypometabolic in u nresponsive patients and regains metabolic activity when the patient recovers signs of awareness [6,46,47]. Moreover, data obtained in sleep (for a review e.g., see [48]) and general anaesthesia (for a review e.g., see [49]) also corroborates these findings.…”
Section: Measuring Consciousnessmentioning
confidence: 99%